Pendidikan Psikologi Anak ”Anti Bullying” pada Guru-Guru PAUD - Sri Rejeki (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
The case of bullying often affects children, both at home and at school. Even in school kindergarten (TK) or at Early Childhood Education (ECD) also cases of bullying. Children's early childhood was the golden age in which cognition, emotion and physically is undergoing rapid development. It takes skill of teachers to recognize, identify and overcome. Teachers as a companion of children in school need training in child psychology, especially in dealing with cases of bullying in order to give a proper stimulant in shaping the personality of the child character. The success handler bullying include many factors that surround, the readiness of educators, environmental conditions protégé, to the learning environment that is used in educating.